Borderland films : American cinema, Mexico, and Canada during the Progressive era - Brégent-Heald, Dominique, 1973- (University of Nebraska Press, 2015)
"An examination of the intersection of North American borderlands and culture, as portrayed through early twentieth-century cinema"--